Dampak Pelanggaran Perjanjian Internasional Antara Negara Dan Organisasi Internasional - Alex Sandro Tomio; Richard Marsilio Was; Dyah Ridhul Airin Daties (Faculty of Law Universitas Pattimura, 2026)
Indonesia is known as one of the world's largest nickel producers. The Indonesian government took a controversial step by implementing a ban on the export of raw nickel ore, effective January 1, 2020. This policy created new dynamics in the international trade system and sparked various debates regarding international law and its economic impact on the national economy. This research aims to examine diplomatic relations between countries and international organizations and to determine the legal implications if diplomatic relations between countries and international organizations are disrupted due to violations of international agreements. The method used in this research is normative juridical research, with conceptual, legislative, and case studies approaches. The results show that countries and international organizations are subjects of international law that can be bound by international agreements. If a violation of these agreements occurs, the violating country can be held accountable under international law through dispute resolution mechanisms available within the relevant international organization. In the case of Indonesia's nickel export ban, the dispute was resolved through the WTO dispute settlement mechanism, which assesses the compliance of national policies with the provisions of international trade agreements.